New records of Anastrepha (Diptera: Tephritidae) primarily from Colombia - Clavijo, Pedro Alexander Rodriguez; Norrbom, Allen L.; Peñaranda, Emilio Arévalo; Tehran, Francisco Balseiro; Díaz, Paula Andrea; Benitez, Maria Clara; Gallego, Jeisson; Cruz, Maria Isabel; Montes, José M.; Rodriguez, Erick J.; Steck, Gary J.; Sutton, Bruce D.; et al. (Zootaxa, 2018)
New distribution information, primarily from Colombia, is provided for 60 species of Anastrepha, including the first records of 33 species from Colombia: A. acca Norrbom, A. acris Stone, A. amita Zucchi, A. amplidentata Norrbom, A. atrox (Aldrich), A. barbiellinii Lima, A. bezzii Lima, A. canalis Stone, A. cocorae Norrbom & Korytkowski, A. compressa Stone, A. cordata Aldrich, A. crebra Stone, A. cryptostrepha Hendel, A. cryptostrephoides Norrbom & Korytkowski, A. furcata Lima, A. fuscicauda Norrbom & Korytkowski, A. galbina Stone, A. grandicarina Norrbom & Korytkowski, A. hamata (Loew), A. katiyari Norrbom, A. macrura Hendel, A. margarita Caraballo, A. minuta Stone, A. nigripalpis Hendel, A. normalis Norrbom, A. pastranai Blanchard, A. pseudanomala Norrbom, A. pulchra Stone, A. similis Greene, A. speciosa Stone, A. urichi Greene, A. willei Korytkowski, and A. zuelaniae Stone. In addition, A. acris is reported from Costa Rica, A. alveata Stone from El Salvador, A. antunesi Lima and A. bahiensis Lima from Bolivia, A. barbiellinii from Trinidad & Tobago, A. bezzii, A. canalis, A. coronilli Carrejo & González, A. cryptostrepha and A. minuta from Bolivia, and A. willei from Argentina and Bolivia. A list of the 83 species of Anastrepha now known to occur in Colombia is provided, as well as illustrations of at least the wing and aculeus tip or male genitalia for 60 species.